Perception of Students of Poltekkes Kemenkes Makassar about Side Effects Incurred After Covid-19 Vaccine - Kartika, Ayuk; Rusli, Rusli; Dewi, Ratnasari (Journal of Health and Nutrition Research, 2023)
Perception is an experience, event, or relationship obtained by inferring and interpreting information. Adverse drug effects are unwanted drug effects that are predicted in advance and within the limits of the therapeutic dose. The purpose of this study was to find out the perceptions of students at the Makassar Ministry of Health Poltekkes regarding the side effects caused by the COVID-19 vaccine. This type of research is a type of descriptive research in the form of a survey with a cross-sectional design. Data collection was carried out by sending questionnaires online to students of the Makassar Ministry of Health Poltekkes who were willing to fill out the questionnaire after receiving it via WhatsApp. The sample in this study was 100 students of the Makassar Ministry of Health Poltekkes. Using a simple random sampling technique, which is a random sampling procedure. The results showed that the perceptions of Makassar Health Polytechnic students towards the side effects caused after the COVID-19 vaccine and the side effects felt by Makassar Polytechnic students after the COVID-19 vaccine were in the category of moderate side effects